2022
DOI: 10.5430/jct.v11n4p139
|View full text |Cite
|
Sign up to set email alerts
|

Counter-Text as a Tool of Psycholinguistic Diagnosing Comprehension of Foreign Language Utterance

Abstract: The research built on the anthropological approach to text comprehension links philosophical and psycholinguistic perspectives of speech perception. The article analyzes the factors influencing adequate comprehension when perceiving foreign language oral speech, in terms of testees’ approximately similar level of language competence and linguo-psychic characteristics. The object of research is counter-texts defined as those fixed in written form samples of а recipient’s internal speech emerging in the process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Semantic differentiations, significant from an anthropological or cultural point of view, which are related to gender variability were revealed by (Soloviova et al, 2021). Another research showed that understanding is marked by a small number of deviations from the author's idea when, firstly, a recipient has a rather wide cultural scope, which provides points of coincidence of dominant knots of the communicant and recipient, and, secondly, he or she has verbal thinking (Formanova et al, 2022).…”
Section: Introductionmentioning
confidence: 95%
“…Semantic differentiations, significant from an anthropological or cultural point of view, which are related to gender variability were revealed by (Soloviova et al, 2021). Another research showed that understanding is marked by a small number of deviations from the author's idea when, firstly, a recipient has a rather wide cultural scope, which provides points of coincidence of dominant knots of the communicant and recipient, and, secondly, he or she has verbal thinking (Formanova et al, 2022).…”
Section: Introductionmentioning
confidence: 95%
“…Contemporary linguists study the structural, semantic, functional and cognitive peculiarities of the professional (specialized) terminology (Cabre, 1999;Formanova, 2022;Hromova, 2022;Kurakh, 2016;Kyrda-Omelian, 2022;Soloviova, 2021). Some scholars made comparative analysis of the English and German termformation in the legislative documents on the basis of the Schengen Border Code Vol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The necessity of providing foreign language training based on modelling the high-risk environment considering psychological support of the students at international relations faculties was substantiated in the studies of (Lysenko, et al, 2020;Kyrda-Omelian, et al, 2022). Psycholinguistic issues of text comprehension of foreign language utterance were revealed by (Batrynchuk, et al, 2022;Formanova, et al, 2022).…”
Section: Theoretical Analysis Of the Problemmentioning
confidence: 99%